Complete Heart Block in Pregnancy: A Curable Entity - Farah Shaukat; Shama Chaudhry; Rubina Hussain (ziauddin University, 2024)
Pregnancy complicated complete heart block is a high-risk situation. Maternal complete heart block (CHB), which manifests for the first time during pregnancy and peurperium, poses a challenge to treating physicians. Pace maker insertion is recommended early in case the patient is symptomatic or has a prolonged Q-T Interval or left atrial enlargement on ECG. We are reporting a case of a pregnant woman G 2 para1+0 with 31 weeks of pregnancy complete heart block. She presented complains of sudden onset of localized epigastric pain which was accompanied with  shortness of breath and non-projectile vomiting. Apart from these symptoms, she did not feel any palpitation. She was conscious and oriented with a pulse rate 44 bpm and BP 151/71mmHg. ECG confirmed the diagnosis of complete heart block. A permanent pacemaker was placed. She delivered at 37 weeks of gestation with an alive & healthy baby by caesarean section due to ruptured membranes. When a multidisciplinary approach is used, both maternal and neonatal outcomes are good.  KEY WORDS Pacemaker, Complete Heart Block (CHB), Q-T Interval.